Effectiveness of a combination therapy of traditional Chinese medicine and CO2 laser treatment for condyloma acuminatum. Issue 12 (3rd May 2020) - Xu, Huaxiang; Shen, Qinglin; Fan, Bing; Xi, Changqing; Wang, Lili
Abstract: Background: Condyloma acuminatum (CA) is both highly infectious and frequently recurring and requires long‐term, repeated treatments, which seriously affect the physical and psychological health of patients. The purpose of the present study was to investigate the effectiveness of a combination therapy of traditional Chinese medicine and CO2 laser on CA and the relationship between CA relapse and cellular immunity. Methods: The study cohort consisted of 160 CA patients who underwent ambulatory treatment between January 2017 and January 2019 in the Department of Dermatology and Venerology of our hospital. The 160 patients were randomly divided into two groups: a combination therapy group (80 cases), who underwent CO2 ‐laser treatment followed by three courses of oral traditional Chinese medicine and a control group (80 cases), who were only treated with the CO2 laser to remove warts. The efficacy of the CO2 ‐laser treatment was evaluated on the first month after treatment and relapse was evaluated at monthly follow‐ups for 6 months. Additionally, 20 normal volunteers were also recruited. Three months before and after treatment, the cellular immunity factors of peripheral blood T lymphocyte subsets, including CD4+, CD8+, CD4+/CD8+, and interleukin‐2 (IL‐2), were detected and compared between CA patients and normal volunteers, the combination therapy and control groups, and the relapse and cure groups to determine whether there were statistical differences. Results: Compared with normal volunteers, CA patients exhibited lower CD4+, CD4+/CD8+, and IL‐2 levels and higher CD8+ levels ( P < .05). In addition, the rates of relapse for the combination therapy and control groups were 25.7% and 40.8%, respectively. However, the comprehensive immunity factors showed no statistical difference ( P > .05) before treatment. Three months after treatment, factors including CD4+ and CD4+/CD8+ were higher in the combination therapy group than in the control group ( P < .05), and CD8+ and IL‐2 showed no statistical difference ( P > .05); factors including CD4+, CD4+/CD8+, and IL‐2 were higher and CD8+ was lower in the cure group than in the relapse group ( P < .05). Conclusion: The therapy combination of traditional Chinese medicine and CO2 ‐laser treatment can reduce the relapse rate of CA. It might be that traditional Chinese medicine combined with CO2‐laser treatment regulate liver meridian, Qi and blood, and restore the balance between various subgroups. Highlights: The therapy combination of traditional Chinese medicine and CO2‐laser treatment can reduce the relapse rate of CA. It might be traditional Chinese medicine combined with CO2‐laser treatment regulate liver meridian, Qi and blood.